A robust control scheme for grid-connected photovoltaic converters with low-voltage ride-through ability without phase-locked loop. (January 2020) - Sabir, Adeel; Ibrir, Salim
Abstract: A robust control scheme with low-voltage ride-through ability is presented for grid-connected photovoltaic converters that operate under harsh conditions such as voltage sags and unknown disturbances and parameters. The proposed strategy allows for flexible active and reactive power injection into the grid during asymmetrical voltage sags without using a phase-locked loop or positive and negative sequence components. In addition, the same controllers are used under both normal operation and voltage sags, thus, lowering the control system's complexity. The scheme is conceived by combining uncertainty-and-disturbance-estimation compensation and repetitive control for the dc voltage and phase currents, respectively. Controller design is carried out systematically and closed-loop stability is proven through Lyapunov's analysis. Several simulation case studies are presented using the SimPowerSystems TM toolbox of MATLAB/Simulink computing environment to demonstrate the performance of the proposed control system under voltage sags, unknown disturbances, abrupt changes in operating conditions, and parametric uncertainties. Highlights: An efficient control scheme for grid-tied photovoltaic converters with LVRT ability. Able to provide dynamic power support to the grid during unbalanced conditions. No requirement for a phase-locked loop or positive-negative sequence decomposition. Ability to seamlessly integrate additional generation without controller redesign.